Never tempt a scot eaudiobook - Smith, Lauren (The League of Rogues, 2020)
Scottish rogue Brodie Kincade has never met a woman he didn't like . . . or didn't want to seduce. And he's about to meet his match in sweet-tempered, often overlooked Lydia Hunt, an English lady he mistakes for her scheming sister who hopes to snatch him up for a husband. Contains mature themes.